Cough in Children: Mechanisms and Approaches to the Treatment - I.L. Vysochina; O.Ye. Chernyshоva (Zaslavsky O.Yu., 2013)
The article deals with the features of the mechanisms of cough and the need for differentiated choice of drugs in the treatment of cough in children.